(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Planning and executing strategies for language acquisition relies heavily on students’ perspectives on the topic. At the high school level, this research intends to examine students’ perspectives on the value of literature in language acquisition. Another goal of this research is to show how different schools’ pupils think. Students’ perspectives on the value of literature in education are examined through a holistic lens by researchers. Using an open-ended questionnaire, researchers surveyed students to gauge their opinions on the value of literature in language acquisition. The study included 555 high school students from 15 different schools. Most students had a good impression, according to the study’s results, meaning that studying literature while learning English helps with the linguistic parts of the language. Beginning with the language approach and working their way down to the context approach, the reader’s approach, and finally the text approach determine, in descending order of importance, how students perceive literature’s value. Combining linguistics with context is the most reasonable strategy. Pedagogical and methodological variables explain in part why certain students’ experiences vary from the study sample when it comes to the positive effects of learning on language support abilities. According to the findings, educators may examine and take into account students’ points of view on the value of literature as a tool for language acquisition.